What Have Advances in Transcriptomic Technologies Taught us About Human White Matter Pathologies? - Jäkel, Sarah; Williams, Anna (Frontiers in Cellular Neuroscience, 2020)
For a long time, post-mortem analysis of human brain pathologies has been purely descriptive, limiting insight into the pathological mechanisms. However, starting in the early 2000s, next-generation sequencing (NGS) and the routine application of bulk RNA-sequencing and microarray technologies have revolutionized the usefulness of post-mortem human brain tissue. This has allowed many studies to provide novel mechanistic insights into certain brain pathologies, albeit at a still unsatisfying resolution, with masking of lowly expressed genes and regulatory elements in different cell types. The recent rapid evolution of single-cell technologies has now allowed researchers to shed light on human pathologies at a previously unreached resolution revealing further insights into pathological mechanisms that will open the way for the development of new strategies for therapies. In this review article, we will give an overview of the incremental information that single-cell technologies have given us for human white matter (WM) pathologies, summarize which single-cell technologies are available, and speculate where these novel approaches may lead us for pathological assessment in the future.